2006
DOI: 10.1103/physrevb.73.033407
|View full text |Cite
|
Sign up to set email alerts
|

COadsorption onCePt(111)studied with LEED, XPS, and temperature programmed desorption

Abstract: CO adsorption on Ce-Pt͑111͒ has been studied by temperature programmed desorption ͑TPD͒, low energy electron diffraction ͑LEED͒ and x-ray photoelectron spectroscopy ͑XPS͒. Thin layers ͑1 to 3 ML͒ of Ce on Pt͑111͒ form upon annealing to 1000 K a surface alloy which most likely is Pt terminated. The CO overlayer structure on Ce-Pt͑111͒ at saturation coverage is argued to be an intermediate between ͑2 ϫ 2͒ and c͑4 ϫ 2͒ superstructures. This intermediate structure exhibits a c͑4 ϫ 2͒ LEED pattern in which some of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…The similar downshift of CO desorption by surface alloying with other metals has also been reported, e.g. on Pt-Sn [35] and Pt-Ce [36] surfaces. Therefore, the results indicate that the 270 peak observed on the Pt particles originates from Fe migration onto the Pt particles or partial Pt-Fe intermixing upon heating to elevated temperatures.…”
Section: Resultssupporting
confidence: 83%
“…The similar downshift of CO desorption by surface alloying with other metals has also been reported, e.g. on Pt-Sn [35] and Pt-Ce [36] surfaces. Therefore, the results indicate that the 270 peak observed on the Pt particles originates from Fe migration onto the Pt particles or partial Pt-Fe intermixing upon heating to elevated temperatures.…”
Section: Resultssupporting
confidence: 83%
“…Previously published results on Pt-terminated surface alloys based on the rare earths La and Ce showed that the desorption temperature for CO desorption may be dramatically lowered. [16][17][18] In the present case of the change in Pt electronic structure on a weakly interacting substrate, such as graphite, the mechanism of electronic structure change is likely to be different than in the case of alloying. It is noted that the reduction in thermal desorption temperature occurs for effective dimensions of the Pt structures in the size range where distinct electrostatic core level shifts are observed, namely a few nanometers.…”
Section: Discussionmentioning
confidence: 93%
“…An increase in chemisorption energy is expected as the centre of the d-band moves to lower binding energies [22,23]. For example, adsorption/desorption properties of CO on Pt terminated rare earth/Pt(111) surface alloys have been found to be dramatically changed as compared to the Pt(111) single crystalline surface [24,25]. An explanation of the rather large reduction in reactivity on the Pt terminated surface alloy was argued to be related to the existence of strong resonant interactions of the Pt d-band with the CO 5 orbital that give rise to a pronounced 5 donor contribution to the CO-Pt bond [26].…”
Section: Discussionmentioning
confidence: 97%